Aging Alters Cervical Vertebral Bone Density Distribution: A Cross-Sectional Study - Eun-Sang Moon; Seora Kim; Nathan Kim; Minjoung Jang; Toru Deguchi; Fengyuan Zheng; Damian J. Lee; Do-Gyoon Kim (Applied Sciences, 2022)
Osteoporosis reduces bone mineral density (BMD) with aging. The incidence of cervical vertebral injuries for the elderly has increased in the last decade. Thus, the objective of the current study was to examine whether dental cone beam computed tomography (CBCT) can identify age and sex effects on volumetric BMD and morphology of human cervical vertebrae. A total of 136 clinical CBCT images were obtained from 63 male and 73 female patients (20 to 69 years of age). Three-dimensional images of cervical vertebral bodies (C2 and C3) were digitally isolated. A gray level, which is proportional to BMD, was obtained and its distribution was analyzed in each image. Morphology, including volume, heights, widths, and concavities, was also measured. Most of the gray level parameters had significantly higher values of C2 and C3 in females than in males for all age groups (p < 0.039). The female 60-age group had significant lower values of Mean and Low5 of C2 and C3 than both female 40- and 50-age groups (p < 0.03). The reduced BMD of the female 60-age group likely resulted from postmenopausal demineralization of bone. Current findings suggest that dental CBCT can detect age-dependent changes of cervical vertebral BMD, providing baseline information to develop an alternative tool to diagnose osteoporosis.